3D-Printed Ergonomic Tool Handles - Rheianne Mae C. Herrera; Ma. Andrea T. Blanco; John Carlo C. Carabeo; Faye Dannah B. Ramilo; John Renmar D. De Silva; Neil Oliver M. Nuqui; Michaela Tayag Espino; Brian J. Tuazon; John Ryan C. Dizon (Universitas PGRI Semarang, 2022)
Although hand tools serve as an instrument for extending one’s capabilities through the use of hands, the comfort it brings is important especially since the welfare of the user is at stake. Aside from using the hand tools repetitively and with an awkward posture, the tool handle compositions and design also contribute to accumulating some work-related musculoskeletal disorders that require further attention in the long run. To provide a long-term solution, 3D-printed new designs of six commonly used hand tools that fit the average hand measurements of Filipinos have been developed. The hand tools are printed using two filaments namely; thermoplastic polyurethane (TPU) which was found to be skin-friendly and polylactic acid (PLA) which is proven to be more functional, both are used on the outer and inner layer of the handle, respectively. The 3D-printed tool handles were evaluated through the use of a comfort questionnaire for hand tools distributed to 10 respondents per tool handle testing, results show that 3D-printed tool handles are found to be more comfortable and convenient rather than the commercial ones. Meanwhile, the researchers note that the adequate length of tool handles may also vary according to functions and not rely alone on the average hand measurements.